The role of Higher Education Institutions (HEIs) in the creation and maintenance of innovation ecosystems in cities – the case of Centro Universitário Cidade Verde (UniCV) - Favero, Marcela Bortotti; Silva, Patrícia Rodrigues da (Revista Nacional de Gerenciamento de Cidades, 2022)
This article discusses the role of higher education institutions in creating and maintaining innovation ecosystems in cities. The same is justified because innovation is key to the development of smart and sustainable cities, and the Educational Institution is responsible for training professionals able to innovate, thus contributing to the improvement of cities. The work, of a qualitative nature, being the research of the exploratory and descriptive type, was carried out through the strategy of the case study of Smart Space - Environment of Innovation of the Centro Universitário Cidade Verde (UniCV), based in the city of Maringá-PR. As a result, it was identified that the innovation environment promotes several actions to promote and train entrepreneurship and innovation, serving students at different stages of interest in entrepreneurship, such as those curious, with entrepreneurial profiles and entrepreneurs. From the above, we understand that the studied environment contributes to the training of professionals with a keen eye for innovation, who will be able to act within organizations solving problems (intrapreneurship) or opening new businesses. In both cases, these professionals will contribute to local development and also, in the search for solutions for urban development, ratifying the relevance of HEIs in the creation and maintenance of innovation ecosystems in cities.